506 Uneventful pseudoaneurysm of the ascending aorta with sternal erosion in pregnancy. (17th December 2020) - Benedetti, Alice; Del Monte, Alvise; Rubino, Maurizio; Mancuso, Daniela
Abstract: A 36-year-old woman at 31 weeks' gestation presented with exertional dyspnoea and palpitations. She had a history of bicuspid aortic valve treated with surgical aortic valvotomy for severe stenosis, followed by ascending aorta replacement for type A acute aortic dissection and Bentall operation with a mechanical valve for severe aortic regurgitation. Eight years after the last surgery, magnetic resonance angiography showed aortic arch aneurysm (49 mm) with a small intimal flap. Thereafter, the patient was lost to follow-up until the current admission. She was hemodynamically stable on presentation and physical examination was unremarkable apart from a mechanical second heart sound. The electrocardiogram showed sinus rhythm with left bundle branch block (Panel A). Transthoracic echocardiography revealed severe left ventricular dilation (EDV 90 ml/m2) with mild dysfunction (EF 50%), normal prosthetic aortic valve function, and aortic arch dilation (50 mm) (Panel B and C). After a multidisciplinary evaluation, elective cesarean section was performed at 34 weeks' gestation. A post-delivery aortic computed tomography angiography revealed aortic arch aneurysm (52 mm) with intimal flap and two pseudoaneurysms of the anterior aortic wall causing sternal erosion (Panel D, E, F and G). Subsequently, the patient underwent ascending aorta and aortic arch replacement by Frozen Elephant Trunk technique with a 24 x130 mm prosthesis between the aortic root and the descending aorta. The postoperative course was uneventful, and the patient was discharged to a cardiac rehabilitation centre.